Reactive distillation configuration for the production of ethyl acrylate - Gore, Jayram I.; Mahajani, Sanjay M.; Mali, Nilesh A. (CHEMICAL ENGINEERING AND PROCESSING-PROCESS INTENSIFICATION, 2024)
Keywords: ACETIC-ACID; CYCLOHEXYL ACETATE; Design; Dimethyl carbonate

Feasibility study of reactive chromatography for the synthesis of 2-ethoxyethyl acetate using the amberlyst-15 catalyst - Gore, Jayram I.; Nadeem, Mohd; Mahajani, Sanjay M.; Mali, Nilesh A. (Industrial & Engineering Chemistry Research, 2025)
Reactive chromatography is a promising process intensification technology that combines reaction and separation in a single piece of equipment. In this study, the reaction kinetics and adsorption behavior of esterification of 2-ethoxyethanol (EC) with acetic acid (AcOH) using Amberlyst-15 as a catalyst are studied using batch reactions and reactive chromatography. Batch reactions are performed to study the kinetic behavior, and an appropriate kinetic model is proposed. To evaluate adsorption parameters, nonreactive separation experiments are performed in a fixed bed chromatographic reactor (FBCR), and results are compared with model predictions. Further, the MATLAB simulations are performed for reactive separation using kinetics and adsorption data, and results are validated by the experiments. Experimentally obtained breakthrough profiles of FBCR for reaction and desorption reveal the applicability of reactive chromatography for the synthesis of ethyl cellosolve.

Effect of sulfonation density on acid strength in ion exchange resins: Insights from solid-state NMR and density functional theory - Tumulu, Goutam Narayan; Datar, Sarvesh; Shelke, Ankita; Swain, Gitanjali; Ajithkumar, T. G.; Thirumalaiswamy, Raja; Mohan, Ojus; Mahajani, Sanjay M. (Molecular Catalysis, 2026)
Ion-exchange (IE) resins are widely used as solid acid catalysts; however, their surface acidity remains poorly characterized because their limited thermal stability precludes conventional NH3-based acidity measurements. Moreover, acid-site accessibility in IE resins is strongly governed by solvent- or reactant-induced swelling. Here, we investigate the surface acidity of commercial Amberlyst and Indion IE resins using & sup3;& sup1;P MAS NMR (Magic Angle Spinning Nuclear Magnetic Resonance), employing TMPO as a molecular probe dispersed on the resin with moderately swelling dichloromethane, thereby capturing the swollen-state acidity relevant for predicting catalytic activity. The deconvolution of the P-31 MAS NMR spectra reveals three distinct acid-strength zones arising from inhomogeneous sulfonation of the polymer matrix. The overall acidity, quantified by the area-weighted average P-31 chemical shift (delta), increases monotonically with sulfonation density. Notably, only resins containing acid sites stronger than similar to 80 ppm exhibited measurable catalytic activity in alpha-pinene isomerization, establishing a direct correlation between acidity and activity. Density functional theory (DFT) calculations on representative resin models, supported by electron-density analyses, attribute the enhancement of acid strength at higher sulfonation densities to cooperative hydrogen-bonding networks among neighboring sulfonic acid groups. Together, these findings establish P-31 MAS NMR-derived surface acidity as a catalytically relevant descriptor for the rational selection of IE resins in liquid phase acid-catalyzed chemistries.
Keywords: Acid strength; Density functional theory; heterogeneous catalysis; Ion-exchange resins; Solid acids; Solid-state NMR